THE CHALLENGES OF PHARMACY EDUCATION IN THE SUDAN - Al Zain Haga, Mohamed; Ibrahim Elnima, Elamin (Gezira Journal of Health Sciences, 2009)
Active steps to establish a college of pharmacy affiliated to University of Khartoum began in the early 1960s.The graduation of the first batch of pharmacists dated back to 1968.  Five academic years, including a preliminary one, are required to obtain the degree, B. Pharm. The applied disciplines taught in the 1960(s) in many parts of the world were: Pharmaceutical Chemistry Pharmaceutics. Pharmacology and Pharmcognosy.  The basic subjects which preceded the applied courses comprised mainly pure chemistry, botany, zoology, human physiology, biochemistry, mathematics and physics.